PERFORMANCE EVALUATION OF TRACTOR OPERATED SIX ROW PLANTER-CUM-FERTILIZER DRILL FOR MILLETS and OTHER CROPS - UTTAM KUMAR,; SUMAN KUMAR PANDIT, (The Journal of Research ANGRAU, 2026)
Millets are the most useful grain crops as they are nutritious and can withstand climate  changes.Performance evaluation of tractor operated 6 row planter with fertilizer drill for millet multi crops (CIAE design) were carried out to determine the field efficiency, effective field capacity and time required to plant during years, 2022-23 and 2023-24. The field capacity of the planter was 0.32 hah-1 with field efficiency 53.87 percent. The average depth of sowing was 55 mm. The cost of operation of tractor operated millet planter on  finger millet crop was found Rs.2084 ha-1 whereas in traditional method it was Rs.8283 ha-1. Thus, there was a saving of amount Rs.6199 ha-1. The performance of the tractor operated 6 row planter with fertilizer drill for millet –multi crops (CIAE design) was found satisfactory and economical and can be adopted for millet and other  crops (small grains) planting by small land holding farmers.